Implementasi model Numbered Head Together Dengan Bantuan Buku Saku Dilengkapi LKS TTS Untuk Meningkatkan Hasil Belajar Kognitif dan Afektif di SMP Negeri 2 Karera - Mayesti Rambu Jati; Anita Tamu Ina; Yoin Meissy Matulessy (BEST Journal (Biology Education, Sains and Technology), 2025)
Background: This study aims to determine the Numbered Head Together model using the help of pocket book media equipped with TTS LKS to improve cognitive and affective learning outcomes of students at SMP Negeri 2 Karera. The type of research is Classroom Action Research (CAR) developed by Kemmis Taggar which is carried out from pre-cycle, cycle I and cycle II. Where each cycle includes the planning, implementation, observation and reflection stages. The subjects of the study were 31 students in grade VIII. Data collection techniques used test, affective assessment rubric and documentation. Data analysis techniques used quantitative descriptive by relying on statistics to analyze the test results given to students to determine the increase in student learning achievement and affective assessment sheets which include mutual cooperation, independence and self-confidence. The results showed an increase in student learning achievement in the cognitive and affective domains of students from the pre-cycle there were 25.80%, cycle I reached 58.08%, and experienced an increase in learning achievement in cycle II to 90.32%. In the aspect of students' affective assessment, from the pre-cycle with a very poor category (19.35%), cycle I with a sufficient category (54.83%) and in cycle II there was an increase with a very good category (90.32%), so that the implementation of the numbered head together model with the help of pocket books equipped with LKS TSS is effective in improving students' cognitive and affective learning outcomes at SMP Negeri 2 Karera.